ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM PENGADILAN NEGERI DALAM PUTUSAN NOMOR 73/Pdt.G/2024/PN Ptk - NIM. A1012211099, PUTRI WELI YULIANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThe judicial process plays an important role in resolving disputes and ensuring justice in society. This research focuses on the juridical analysis of the judge's legal considerations in Decision Number 73/Pdt.G/2024/PN Ptk related to a breach of contract dispute in the business relationship between Wahana Duta Jaya Rucika Ltd. and Ariesta Sukses Makmur Ltd. (Defendant I) and Mr. Aziz Muslim (Defendant II). This study aims to analyze the basis of the judge's legal considerations and identify the legal consequences for the parties involved. The research method used is normative juridical with a legislative approach and a case approach. The data used includes primary, secondary, and tertiary legal materials, which are analyzed through systematic interpretation. The results of this research show that the judge's legal considerations were correct, based on the principle of Pacta Sunt Servanda and Article 1338 of the Civil Code. The judge considered that the Plaintiff had provided strong evidence of Defendant I's breach of contract, and the rejection of the claim for interest and penalties indicated that the judge adhered to the agreement terms. The legal consequence for the Plaintiff is the right to demand payment settlement through execution, while Defendant I is obliged to settle the outstanding debt and bear the litigation costs, while Defendant II is not personally liable, so the legal obligation is fully on Defendant I.Keywords: Breach of Contract, Judge's Legal Considerations, Legal Certainty Abstrak Proses peradilan memiliki peran penting dalam menyelesaikan sengketa dan memastikan keadilan dalam masyarakat. Penelitian ini berfokus pada analisis yuridis terhadap pertimbangan hukum hakim dalam Putusan Nomor 73/Pdt.G/2024/PN Ptk yang berkaitan dengan sengketa wanprestasi dalam hubungan dagang antara PT. Wahana Duta Jaya Rucika dan PT. Ariesta Sukses Makmur (Tergugat I) serta Tn. Aziz Muslim (Tergugat II). Penelitian ini bertujuan untuk menganalisis dasar pertimbangan hukum hakim dan mengidentifikasi akibat hukum bagi para pihak. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Data yang digunakan meliputi bahan hukum primer, sekunder, dan tersier, yang dianalisis melalui penafsiran sistematis. Hasil Penelitian ini menunjukkan bahwa pertimbangan hukum hakim sudah tepat, berdasarkan prinsip Pacta Sunt Servanda dan Pasal 1338 KUHPerdata. Hakim menilai Penggugat telah memberikan bukti kuat terkait tindakan wanprestasi Tergugat I, penolakan tuntutan bunga dan denda menunjukkan hakim berpegang pada kesepakatan dalam perjanjian. Akibat hukum bagi Penggugat adalah hak untuk menuntut pelunasan pembayaran melalui eksekusi, sementara Tergugat I wajib melunasi hutang sisa pembayaran dan menanggung biaya perkara, sedangkan tergugat IItidak dibebani tanggung jawab pribadi, sehingga kewajiban hukum sepenuhnya ada pada Tergugat IKata Kunci: Wanprestasi, Pertimbangan Hukum Hakim, Kepastian Hukum.